Grain quality evaluation of world rices - Juliano, Bienvenido O. (International rice research institute, 1993)
This book updates and expands the 1980 IRRI publication Quality characteristics of milled rice grown in different countries by Juliano and C. G. Pascual. It provides the data base of selected grain quality characteristics of milled rice from all countries producing more than 0.1% of the world’s rice. Quality characteristics and preferences are discussed by country based on information obtained from national programs.